Health-Related Quality of Life Dynamics of HIV-positive South African Women up to ART Initiation: Evidence from the CAPRISA 002 Acute Infection Cohort Study - Tomita, Andrew (2014)
Few studies have investigated the long-term dynamics in health-related quality of life (HRQoL) among HIV-positive persons from acute infection. From 2004, 160 women were enrolled into the CAPRISA 002 Acute Infection study at two sites in the province of KwaZulu-Natal and underwent 3–6 monthly HRQoL assessments using the functional assessment of HIV infection (FAHI) instrument. Overall and 5 sub-scale FAHI scores [physical well-being (PWB), emotional well-being (EWB), functional and global well-being (FGWB), social well-being (SWB) and cognitive functioning (CF)] were calculated up to antiretroviral therapy (ART) initiation and scores at enrollment were compared to the acute, early and established infection phases. Mixed-effects regression models adjusting for behavioral and clinical factors were applied to assess HRQoL trends and the proportion of women meeting minimally important differences was calculated. Our analyses revealed that overall/sub-scale scores improved over time, except from PWB and CF. A higher educational status, contraceptive use and a higher BMI were the strongest predictors of higher overall/sub-scale FAHI scores. CD4 count and HIV viral load were strongly associated with PWB and CF, but not overall FAHI and other sub-scales. Women newly diagnosed with acute HIV infection face profound HRQoL challenges. While early ART delivery may be important for PWB and CF, factors such as education, contraception provision and good nutritional status should be promoted to maximize HRQoL in HIV positive individuals.